2022
DOI: 10.1007/s12061-022-09471-1
|View full text |Cite
|
Sign up to set email alerts
|

Does Long-Term Air Pollution Exposure Affect Self-Reported Health and Limiting Long Term Illness Disproportionately for Ethnic Minorities in the UK? A Census-Based Individual Level Analysis

Abstract: Previous studies have investigated the impact of air pollution on health and mortality. However, there is little research on how this impact varies by individuals’ ethnicity. Using a sample of more than 2.5-million individuals aged 16 and older from the 2011 UK census linked to 10-years air pollution data, this article investigates the effect of air pollution on self-reported general health and limiting long-term illness (LLTI) in five main ethnic groups and by country of birth in UK. The association of air po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…This is because these pollutants have been shown by relevant literature to be related to poor health outcomes. We did not study ozone because this is a seasonal pollutant that interacts with other pollutants in the atmosphere, mostly during the summer [ 2 , 30 , 39 ]. Thus, annual pollution data is not suitable to study the health effects of ozone.…”
Section: Methodsmentioning
confidence: 99%
“…This is because these pollutants have been shown by relevant literature to be related to poor health outcomes. We did not study ozone because this is a seasonal pollutant that interacts with other pollutants in the atmosphere, mostly during the summer [ 2 , 30 , 39 ]. Thus, annual pollution data is not suitable to study the health effects of ozone.…”
Section: Methodsmentioning
confidence: 99%
“… 15 17 There is also mounting evidence of an association between air pollution exposure and increased mental health stress, psychiatric disorders, and cognitive decline. 18 , 19 Air pollution exposure is thus increasingly recognized as a key contributor to the global burden of morbidity, including reduced quality of life and altered health perceptions and well-being, 20 , 21 and has a potentially significant role in premature mortality. 8 , 22 , 23 …”
Section: Introductionmentioning
confidence: 99%
“…The health impacts of medium- and longer-term exposure to air pollution may be modified by multiple social, cognitive, and environmental factors 21 and particularly by other interrelated stressors linked to concentrated socioeconomic disadvantage in neighborhood contexts. Owing to historical and present-day structural inequities, including systemic racism and other forms of oppression, low-income and minoritized populations in the United States tend to be overrepresented in neighborhoods characterized by economic disinvestment and social disruption.…”
Section: Introductionmentioning
confidence: 99%
“…Ethnicity forms an important topic in the health literature (19,20) and might be an important effect modi er in the association between air pollution and health. Ethnic minorities often report poorer health compared to the rest of the population (20)(21)(22)(23)(24). Literature from the UK has shown that people from Pakistani and Bangladeshi origins tend to have the poorest reported health followed by people from African/Caribbean and Indian origins (20,(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…Ethnic minorities often report poorer health compared to the rest of the population (20)(21)(22)(23)(24). Literature from the UK has shown that people from Pakistani and Bangladeshi origins tend to have the poorest reported health followed by people from African/Caribbean and Indian origins (20,(24)(25)(26). This is because ethnic minorities, in general, tend to occupy lower socioeconomic status and live in more deprived ethnic concentration communities with poor housing conditions (20,(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%